2020
DOI: 10.32890/ijbf2019.14.0.9913
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Health Awareness and Knowledge in Medical Takaful Purchase Intention

Abstract: The present study aims to examine the factors of health awareness and knowledge that influence customers’ intention to use medical takaful coverage among the public sector officers in northern Malaysia. A quantitative research methodology was adopted to answer the objectives progressively. In the current research, data from 313 respondents were collected via questionnaires from three different organisations, namely the police department, the fire and rescue firefighter department, and the education department.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In addition to the data above, based on previous journal reviews, there are several other factors that influence consumer purchase intention. As in previous studies, it has been proven that awareness and knowledge are factors that influence consumer buying (Arlanti & Suyanto, 2019;Haji Wahab & Mohd Tajuddin, 2020). In addition, according, quality factors, price perceptions, and brands also have a significant positive effect on purchase intention.…”
Section: Figure 1 Portable Fire Extinguishermentioning
confidence: 53%
“…In addition to the data above, based on previous journal reviews, there are several other factors that influence consumer purchase intention. As in previous studies, it has been proven that awareness and knowledge are factors that influence consumer buying (Arlanti & Suyanto, 2019;Haji Wahab & Mohd Tajuddin, 2020). In addition, according, quality factors, price perceptions, and brands also have a significant positive effect on purchase intention.…”
Section: Figure 1 Portable Fire Extinguishermentioning
confidence: 53%
“…Health awareness, as a factor revealed by this research, plays an important role in shaping consumer preferences and decisions regarding takaful health products. As stated by Zarunnaim et al (2018), the positive and significant relationship between health awareness and consumer knowledge can provide an important impetus in shaping customers' intention to purchase medical takaful. In this context, this study shows that the higher the level of health awareness, the more likely consumers will tend to choose takaful health products.…”
Section: Cluster 5: Health Awareness and Health Takaful Performancementioning
confidence: 99%
“…However, the relationship between health consciousness and customers' purchase intentions toward herbal products and supplements is still divergent. In general, previous research has found that health consciousness has positive and significant effect on customers' purchase intention toward herbal products, supplements, and organic and green products (Widyaningtyas et al, 2023;Handayani & Darmawan, 2022;Wahab & Tajuddin, 2020;Parashar et al, 2023;Damberg, 2022;Shah et al, 2021;Tan et al, 2019). Meanwhile, some researchers fail to find the significant effect of health consciousness on customers' purchase intention toward herbal products, supplements, and organic and green products (Sultan et al, 2019;Asteria & Hati, 2023;Echchad, 2023).…”
Section: Introductionmentioning
confidence: 98%